Innovation in Chemical Plant Design (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Innovation in chemical plant design is driving improvements in efficiency, safety, and environmental sustainability. This progress is influenced by factors such as safety standards, environmental regulations, market dynamics, and technological advancements. Innovations encompass process intensification, modular design, automation, data analytics, and sustainability solutions, addressing modern challenges. These innovations have diverse applications, spanning drug delivery systems, textile technologies, spray drying, extraction, and active packaging. Notably, supercritical fluid-assisted production of liposomes in pharmaceuticals promises improved therapeutic outcomes through meticulous optimization and sustainability. The textile industry sees advancements in natural dyeing and antibacterial properties, while spray-drying and extraction processes enhance product development and sustainability. Integration of remote sensing and microelectronics aids land surface temperature understanding for applications like agriculture and climate change studies. Convolutional Neural Networks benefit material science, facilitating material identification for energy storage and lubrication applications. Techno-economics for gas-to-liquid processes in natural gas are vital for energy and environmental sustainability. The industry's ongoing evolution prioritizes safety, sustainability, and efficiency, relying on innovative approaches and technologies to create safer, more sustainable, and economically viable chemical processes with reduced environmental impact, contributing to a prosperous and sustainable future.